The In-Group Code Lexis - Cutting, Joan (HERMES - Journal of Language and Communication in Business, 2002)
This article provides a developmental description of the lexis used by an academic discourse community in formation. Casual conversations of six post-graduate students, native speakers of English, were recorded in the Applied Linguistics common room in Edinburgh University throughout the 1991-92 course. The central hypothesis was that as common knowledge of the course and shared interpersonal knowledge increase over time, there is an increase in the implicit vocabulary which forms the in-group code, and which depend heavily on the context for their meaning. This article discusses the gradability of contentfulness in lexis in topics about the course, analysing technical terms, proper nouns with metonymical meaning, limited range generic nouns, and general nouns and verbs. It discusses the implicitness of the lexical items that have a pragmatic meaning that only in-group members would understand, and suggests that, for an outsider, the implicitness can be associated with the impenetrability of the dialogue.